Single-Center Experience With Epigenetic Treatment for Juvenile Myelomonocytic Leukemia - Marcu, Andra; Colita, Andrei; Radu, Letitia Elena; Jercan, Cristina Georgiana; Bica, Ana Maria; Asan, Minodora; Coriu, Daniel; Tanase, Alina Daniela; Diaconu, Carmen C.; Mambet, Cristina; Botezatu, Anca; Pasca, Sergiu; et al. (Frontiers in Oncology, 2020)
Background: Juvenile myelomonocytic leukemia (JMML) is a rare myelodysplastic/myeloproliferative neoplasm diagnosed in young children, characterized by somatic or germline mutations that lead to hyperactive RAS signaling. The only curative option is hematopoietic stem cell transplantation (HSCT). Recent data showing that aberrant DNA methylation plays a significant role in pathogenesis and correlates with clinical risk suggest a possible benefit of hypomethylating agents (HMA) in JMML treatment. Aim: The aim is to report the results of HMA-based therapy with 5-azacytidine (AZA) in three JMML patients treated in a single center, non-participating in EWOG-MDS study. Methods: The diagnosis and treatment response were evaluated according to international consensus criteria. AZA 75 mg/m2 intravenous (i.v.) was administered once daily on days 1–7 of each 28-day cycle. All patients were monitored for hematologic response, spleen size, and evolution of extramedullary disease. Targeted next generation sequencing (NGS) were performed after the 3rd AZA cycle and before SCT to evaluate the molecular alterations and genetic response. Results: Three patients diagnosed with JMML were treated with AZA (off-label indication) in Pediatric Department of Fundeni Clinical Institute, Bucharest, Romania between 2017 and 2019. There were two females and one male with median age 11 months, range 2–16 months. The cytogenetic analysis showed normal karyotype in all patients. Molecular analysis confirmed KRAS G13D mutation in two patients and NRAS G12D mutation in one patient. The clinical evaluation showed important splenomegaly and hepatomegaly in all 3 pts. One patient received AZA for early relapse after haploidentical HSCT and the other two patients received upfront AZA, as bridging therapy before HSCT. After HMA therapy, 2/3 patients achieved clinical partial response (cPR), 1/3 had clinical stable disease (cSD) and all had genetic stable disease (gSD) after 3 cycles and were able to receive the planned HSTC. One patient achieved clinical and genetic complete response before HSCT. During 22 cycles of AZA there were only four adverse events but only one determined dose reduction and treatment delay. Conclusion: Our data show that AZA monotherapy is safe and effective in controlling disease both in upfront and relapsed patients in order to proceed to HSCT.